Clinical characteristics of pancreatic and biliary tract cancers in Lynch syndrome: A retrospective analysis from the Finnish National Lynch Syndrome Research Registry - Zalevskaja, Kristina; Mecklin, Jukka-Pekka; Seppälä, Toni T. (Frontiers in Oncology, 2023)
IIntroduction: Patients with Lynch syndrome (LS) have increased lifetime risk of pancreatic cancer (PC) and biliary tract cancer (BTC). These cancers have notoriously pessimistic prognosis due to late diagnosis and limited therapeutic options. There are limited data based on small cohorts reviewing PC and BTC in LS patients. Results: Thirty-nine patients were included: tumour(s) was located in pancreas in 26 patients, in biliary tract in 10 and in ampulla of Vater in 3. Pathogenic germline variant was in MLH1 in 33/39 patients. Twenty-six patients with 28 tumours located in pancreas were identified: 23 pancreatic ductal adenocarcinomas (PDAC) and 5 neuroendocrine tumours (NET). The median age at diagnosis of PC was 64 years (range 38-81). In PC, the 5-year overall survival (OS) rate was 20% and in PDAC 13,6%. Ten patients with BTC were diagnosed: 2 intrahepatic, 5 perihilar, 2 distal extrahepatic cholangiocarcinomas and 1 gallbladder carcinoma. Eight patients were male and the median age at diagnosis was 54 years (range 34-82). The 5-year OS rate in BTC was 30%. Metachronous tumours were diagnosed in 28 patients (70%). Colorectal cancer was the most common metachronous tumour, diagnosed in 20 patients (51%), and prior to PC or BTC in all cases. Curative surgery was attempted in 17/39 patients. For 30 patients (91%), the cause of death was PC or BTC, two patients died from another LS-associated cancer and 1 patient from stroke. Conclusion: Although survival of LS patients with PC or BTC is better than in sporadic cancers, it is still poor, and may be reflected by the relatively higher surgical resectability accounted for by earlier age of onset. More studies on analyses of the molecular and immune profile, screening and management for LS-associated pancreaticobiliary cancers are warranted.